Pengaruh aplikasi plant growth promoting rhizobacteria (PGPR) terhadap cherelle wilt dan kualitas hasil kakao - Yohana Theresia Maria Astuti (Fakultas Pertanian Universitas Yudharta Pasuruan, 2022)
This study aims to reduce cherelle wilt with plant growth promoting rhizobacteria (PGPR) application. The study was conducted in July – December 2021. The study used an experimental method with a completely randomized design. Factor I PGPR applications consist of 3 kinds namely control, EM4 and PGPR. Factor II varietas consist of 2 kinds namely Sul 01 and MCC 01. The results showed that there was no significant interaction between the application of biofertilizer and cocoa varieties. The number of cherelle wilt in the application of PGPR and EM4 was lower that that the control, on the other hand the number of new pods/plant calculated the beginning until 4 months after application of PGPR and EM4 was higher than the control. The weight of 100 cocoa fermented beans in PGPR application was better than EM4 and control. The content of N and P available in the soil in the application of biofertilizer was higher than the control. The number of cherelle wilt and new pods were the same in the different varieties. The conclusion was the application of PGPR decreased the number of cherelle wilt of cocoa, increased the number of new pod, and increased the weight of 100 cocoa fermented bean. The application of PGPR and EM4 increased the available N dan P content in the soil. The difference of variety did not affect on cherelle wilt, but the quality of cocoa beans in MCC 01 was greater than Sul 01.